(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the knowledge and practice of compliance with routine hand hygiene and identify some factors related to the knowledge and practice of routine hand hygiene compliance of nurses and midwives at different departments. Clinical, Obstetrics and Pediatrics Hospital, Quang Ngai Province in 2023. Research method and time: The study applied an analytical cross-sectional research method and was implemented from 9/2022 to 9/2023 with 110 nurses and midwives, observation by checklist and knowledge distribution. Apply descriptive statistics (frequency, percentage) and analytical statistics (test χ2, OR, 95%CI with significant level at p<0.05). Results: 82,7% ofnurses and midwives have acceptable knowledge about routine hand hygiene and the prevalence of routine hand hygiene compliance among them was 31,8%. Factors affecting the knowledge of routine hand hygiene of nurses and midwives included education level, and workplace. Age, overcrowding of patients and inadequate knowledge about bacteriological hygiene tended to reduce the routine hand hygiene compliance of nurses and midwives. Conclusion: While the majority of nurses and midwives had acceptable knowledge about routine hand hygiene, the practical rate was not high equally, it is necessary to continuously update the knowledge on maternal hygiene for nurses and midwives, especially in the Obstetrics and Gynecology blocks.